2013
DOI: 10.2337/dc12-1224
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte/Endothelial Cell Interactions and Mitochondrial Dysfunction in Type 2 Diabetic Patients and Their Association With Silent Myocardial Ischemia

Abstract: OBJECTIVEDiabetes is associated with oxidative stress and increased mortality, but a possible correlation between leukocyte-endothelium interactions, oxidative stress, and silent myocardial ischemia (SMI) is yet to be confirmed.RESEARCH DESIGN AND METHODSMitochondrial dysfunction and interactions between leukocytes and human umbilical vein endothelial cells were evaluated in 200 type 2 diabetic patients (25 with SMI) and 60 body composition– and age-matched control subjects. A possible correlation between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 40 publications
9
59
1
Order By: Relevance
“…4C), which seems to be attributable to MIOXmediated cellular events, because, following its siRNA treatment, the intensity of fluorogenic MBB and the ratio were largely restored. Such changes in the GSH/GSSG ratio have been described in diabetic patients as well (50).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4C), which seems to be attributable to MIOXmediated cellular events, because, following its siRNA treatment, the intensity of fluorogenic MBB and the ratio were largely restored. Such changes in the GSH/GSSG ratio have been described in diabetic patients as well (50).…”
Section: Discussionmentioning
confidence: 96%
“…5). The fact that NOX4 siRNA treatment partially blocked the generation of ROS would also suggest that ROS are derived from dual sources in MIOX-overexpressing cells under high glucose ambience, as has been described in various investigations related to diabetic nephropathy in various animal models (1,3,9,10,50).…”
Section: Discussionmentioning
confidence: 99%
“…Although endothelial dysfunction and endothelial/leukocyte interactions are key features of diabetes and are thought to be a major cause of diabetes-associated vascular complications, the underlying molecular mechanisms remain unclear [14,15]. In the present study, we observed that serum myeloperoxidase levels were significantly increased in type 2 diabetic patients and also positively correlated with ACR indicating its relevance for diagnosis of vascular dysfunction.…”
Section: Discussionsupporting
confidence: 67%
“…Mitochondrial mass was measured in cells treated with the fluorescent dye 10-N-nonyl acridine orange (NAO, 5! 10 K6 mol/l), which specifically binds to cardiolipin independently of DJ m (27).…”
Section: Membrane Potential and Mitochondrial Massmentioning
confidence: 99%
“…A Clark-type O 2 electrode (Rank Brothers, Bottisham, UK) was used to measure O 2 consumption (27). Sodium cyanide (10 K3 mol/l) was employed to evaluate whether or not O 2 consumption was mitochondrial (95-99%).…”
Section: Measurement Of O 2 Consumptionmentioning
confidence: 99%